Students' satisfaction toward University Health Center: a Structural Equation Modelling Approach - Sapiri, Hasimah; Md Yusof, Zahayu; Misiran, Masnita; Mahmuddin, Massudi (UUM Press, 2022)
Students with good health contribute to overall academic performance especially in higher education. In the university campus, university health center provides medical and comprehensive health care services. These services including medical and dental treatment, counseling, first aid, and medication. This research explored the perception of undergraduate student towards health center in UUM Sintok campus by using Structural Equation Model. Based on the investigation, the most influence factor is services, while waiting time does not have influence on the student satisfaction towards the university health center.